Late Miocene to Holocene calcareous nannofossils from ODP sites of Leg 125 - Giuliano Ciampo (PANGAEA, 1992)
During Leg 125 of the Ocean Drilling Program, nine sites were drilled in the Mariana and Izu-Bonin areas. The sediments recovered range in age from early Pliocene to late Pleistocene in the Mariana Region and from middle Eocene to late Pleistocene in the Izu-Bonin region. This contribution concerns the biostratigraphic study of the latest Miocene (CN9b Subzone) to late Pleistocene interval. Aquantitative analysis of all calcareous nannofossil associations was conducted for the interval encompassing late Miocene to the top of the early Pliocene. Moreover, the genera Discoaster, Amaurolithus, and Ceratolithus were quantitatively investigated from the late Miocene to late Pliocene interval. Some bioevents were identified, and variations in the composition of assemblages were linked to climatic changes.
Supplement to: Ciampo, G (1992): Late Miocene (CN9B subzone) to Holocene calcareous nannofossils from the western and northwestern Pacific Ocean, Leg 125. In: Fryer, P; Pearce, JA; Stokking, LB; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 125, 15-41, https://doi.org/10.2973/odp.proc.sr.125.141.1992